Designing Arabic Learning with Prediction Guide: A Prospect - Rahmawati, Fitra Awalia; Kurniawan, Muhammad Ariiq (Proceeding International Conference on Religion, Science and Education, 2022)
The Prediction Guide Learning Strategy is currently used as an active learning method in schools. During the learning process, it is more often defined as an explanation of pictorial material with children making up stories in the pictures that the teacher provides. In the discussion of this paper discusses learning in schools using a prediction guide strategy by analyzing the activeness and thinking of students. By concluding that learning strategies in Indonesia by using learning strategies will change the way of learning and focus on lessons and students will further develop their way of thinking to improve their ability to think. The quality of children's learning will improve the way of thinking and social empathy with classmates. And get new knowledge in using learning strategy methods. The existence of this strategy will affect children's thinking patterns and invite social empathy towards friends around them.